ЕНГИЛ АТЛЕТИКА СПОРТ ТУРИНИ РИВОЖЛАНТИРИШНИНГ ИЛМИЙ-НАЗАРИЙ АСОСЛАРИ - Мамбетов, Б.Ж.; Зарипова, Ф.А. (SCIENCE and SOCIETY, 2017)
The article deals with the issues of the development of physical culture and sports in the country and the author analyzes the impact of social factors to the development of athletics. There have been studied the attitude to athletics, and the social and aesthetic sides of athletics in the society.
Keywords: health; physical education; healthy lifestyle; planning; technology; of development athletics; distance; speed; sensitivity; dexterity